Mouse models of human ocular disease for translational research. - Mark P Krebs; Gayle B Collin; Wanda L Hicks; Minzhong Yu; Jeremy R Charette; Lan Ying Shi; Jieping Wang; Jürgen K Naggert; Neal S Peachey; Patsy M Nishina (PLoS ONE, 2017)
Mouse models provide a valuable tool for exploring pathogenic mechanisms underlying inherited human disease. Here, we describe seven mouse models identified through the Translational Vision Research Models (TVRM) program, each carrying a new allele of a gene previously linked to retinal developmental and/or degenerative disease. The mutations include four alleles of three genes linked to human nonsyndromic ocular diseases (Aipl1tvrm119, Aipl1tvrm127, Rpgrip1tvrm111, RhoTvrm334) and three alleles of genes associated with human syndromic diseases that exhibit ocular phentoypes (Alms1tvrm102, Clcn2nmf289, Fkrptvrm53). Phenotypic characterization of each model is provided in the context of existing literature, in some cases refining our current understanding of specific disease attributes. These murine models, on fixed genetic backgrounds, are available for distribution upon request and may be useful for understanding the function of the gene in the retina, the pathological mechanisms induced by its disruption, and for testing experimental approaches to treat the corresponding human ocular diseases.